SINTESIS ?-ALUMINA DARI NH4(rumus) DAWSONITE SEBAGAI PENYANGGA KATALIS KOBALT-CERIA UNTUK REAKSI FISCHER(rumus)TROPSCH - FAQIHUDDIN ZAKY NIM: 20514002, M
Fischer-Tropsch process is an alternate way to overcome the energy crisis. This process converts synthesis gas (H2 and CO) to hydrocarbon with the presence of metal catalyst. The metal catalysts for Fischer-Tropsch reaction usually require a support to increase their active sites. Gamma alumina (?-Al2O3) is one of the most common catalyst support because of its relatively high specific surface area, large pore size, and have good thermal and mechanical stability. Recently, many attempts have been made to increase the surface area, pore volume and pore size of ?-Al2O3 to increase its capability as a catalyst support. The most common way is to use surfactant or structure directing agent in synthesis process. Altough it has proven to be effective, the expensive cost of surfactants makes it less economical for practical applications. In this study, ?-Al2O3 were synthesized using NH4-dawsonite precursor without any surfactant. NH4-dawsonite were synthesized by coprecipitation method with variations of mixing techniques and pH. In the first method, (NH4)2CO3 solution is added drop-wise to Al(NO3)3 solution with vigorous stirring at 50 oC and aged for 1 day at the same temperature. In the second method, mixing process is reversed, Al(NO3)3 solution is added drop-wise to (NH4)2CO3 solution while stirring and aging process is the same as first method. IR spectra and XRD pattern showed the synthesis using first method resulted in boehmite, and the second method resulted in NH4-dawsonite. Using different aging temperature (100 oC) in the first method resulted in a mixture of boehmite and NH4-dawsonite. Calcination of as-prepared samples at 600 oC for 5 h resulted in ?-Al2O3 and have been confirmed by their XRD patterns. SEM images showed the synthesized ?-Al2O3 either from boehmite or NH4-dawsonite formed agglomerates. The pH of mixture in second method is adjusted to 8, 9, and 10 by adding NH3 solution. TEM images showed that NH4-dawsonite synthesized at higher pH resulted in more aggeragates of ?-Al2O3. Particle size analysis showed the grain size of ?-Al2O3 is larger when NH4-dawsonite is synthesized at higher pH value. N2-physisorption analysis showed the ?-Al2O3 from boehmite precursor has specific surface area of 237,3 m2/g, while ?-Al2O3 from NH4-dawsonite with variation of pH 8, 9, and 10 have specific surface area of 254,0; 275,8; and 305,9 m2/g respectively. ?-Al2O3 from NH4-dawsonite precursor synthesized at higher pH value has higher specific surface area but smaller pore volume and pore size. The synthesized ?-Al2O3 then were used as cobalt-ceria catalyst support for Fischer-Tropsch reaction. Co-Ce/?-Al2O3 catalysts with the weight ratio of Co:Ce:?-Al2O3 9:1:10 were synthesized by incipient wetness impregnation method using Co(NO3)2 and Ce(NO3)3 solution with water-ethanol as solvent. Catalytic activity test for Fischer-Tropsch reaction was carried out using micro fixed bed reactor under atmospheric pressure at 225 oC with flow rate 5 mL/min of syn-gas (H2/CO = 2). The catalysts were reduced in-situ at 350 oC for 6 h with the flow of H2 (8 mL/min) under atmospheric pressure prior to Fischer-Tropsch reaction. The products of reaction were trapped using coldtrap at -195 oC for 3 h. GC analysis results of Fischer-Tropsch products showed that the catalyst using ?-Al2O3 support from NH4-dawsonite precursor has higher activity and selectivity towards hydrocarbon C4+ than catalyst using ?-Al2O3 support from boehmite precursor. The use of ?-Al2O3 support with higher specific surface area resulted in higher activity of Fischer-Tropsch reaction. The use of ?-Al2O3 support with larger pore size and pore volume resulted in better selectivity towards C4+ products. The activity of Fischer-Tropsch reaction and selectivity of C4+ products is decreased with the increase of reaction temperature.